Sensational Subjects The Dramatization of Experience in the Modern World - Jervis, John (The WISH List, 2015)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Under what conditions does 'sensation' become 'sensational'? In the early nineteenth century murder was a staple of the sensationalizing popular press and gruesome descriptions were deployed to make a direct impact on the sensations of the reader. By the end of the century, public concern with the thrills, spills, and shocks of modern life was increasingly articulated in the language of sensation. Media sensationalism contributed to this process and magnified its impact, just as sensation was, in turn, taken up by literature, art and film. In the contemporary world the dramatization of these experiences in an era of media panics over terrorism and paedophilia has taken an overtly melodramatic form, in which battles of good and evil play out across the landscapes of our lives. Sensational Subjects develops an innovative, interdisciplinary approach to exploring these themes, their impact and their implications for understanding the modern world. A companion volume, Sympathetic Sentiments: Affect, Emotion and Spectacle in the Modern World is published simultaneously by Bloomsbury.